2013
DOI: 10.1590/s0047-20852013000200007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnosis of 80 cases of dementia in a university hospital

Abstract: Objective: This study aims to estimate the prevalence of dementia subtypes and to assess the socio-demographic data of patients attending the outpatient clinic of dementia at Hospital das Clínicas from January 2008 to December 2009, in the city of Goiânia-GO, Brazil. Methods: Procedures provided for diagnosis included physical and neurological examination, laboratory tests, neuroimaging and DSM-IV. The functional capacity and level of cognitive deficit were assessed by Pfeffer Functional Activities Questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
5
0
3
Order By: Relevance
“…In tertiary centers-based studies, the frequency of these two etiologies ranged from 3.7% to 15% of cases [9][10][11][12][13] Similarly, a study based on neuropathological diagnosis cases 14 showed that LBD caused 15% of cases of dementia, whether isolated or associated with other pathologies. LBD was also the second most frequent neurodegenerative etiology of dementia and related to a higher risk of dementia with an odds ratio (OR) of 3.4 (CI: 1.94-5.97).…”
Section: Epidemiologymentioning
confidence: 98%
“…In tertiary centers-based studies, the frequency of these two etiologies ranged from 3.7% to 15% of cases [9][10][11][12][13] Similarly, a study based on neuropathological diagnosis cases 14 showed that LBD caused 15% of cases of dementia, whether isolated or associated with other pathologies. LBD was also the second most frequent neurodegenerative etiology of dementia and related to a higher risk of dementia with an odds ratio (OR) of 3.4 (CI: 1.94-5.97).…”
Section: Epidemiologymentioning
confidence: 98%
“…A DDP representa 13,5% dos casos de parkinsonismo com demência 6 , enquanto a DCL é responsável por menos de 5% das etiologias 7,8 . Em estudos baseados nas casuísticas de centros terciários, a prevalência dessas duas etiologias varia entre 3,7 a 15% [9][10][11][12][13] dos casos de demência. Esses dados são similares aos observados em estudo neuropatológico prévio, em que a DCL foi responsável por 15% das etiologias de demência, seja de forma isolada ou associada a outras patologias 14 .…”
Section: Epidemiologiaunclassified
“…In children, a study with 71 confirmed cases showed that 28.17% of the patients had neurological involvement 13 . Another study evaluating 74 patients with possible viral associated neurological complications in Brazil found that 11% of those cases had relationship with DF 14 .…”
Section: Bhushan Et Al (2018) Found 486% Of Immune-mediated Neurolomentioning
confidence: 99%